Ethical Issues in Biotechnology - Russow, Lilly-Marlene (The Hastings Center report, 1994)
Book reviewed in this article: The Code of Codes: Scientific and Social Issues in the Human Genome Project. Edited by Daniel J. Kevles and LeRoy Hood. Wonderwoman and Superman: The Ethics of Human Biotechnology. By John Harris.